The week after running a marathon: Effects of running vs elliptical training vs resting on neuromuscular performance and muscle damage recovery. Issue 12 (2nd December 2021) - Martínez-Navarro, I.; Montoya-Vieco, A.; Hernando, C.; Hernando, B.; Panizo, N.; Collado, E.
Abstract: Our aim was to compare the effects of two exercise modalities vs resting on the time course of neuromuscular performance and muscle damage recovery during the week after running a marathon. Sixty-four finishers from a road marathon completed the study (54 men and 10 women; 39 ± 4 years; 3 h 35 min ± 21 min). The day before the race, within 15 min after finishing the marathon and at 24, 48, 96, 144 and 192 h postrace, lactate dehydrogenase and creatine kinase were analysed. Participants also performed a squat jump (SJ) test before and after the marathon and at 48, 96 and 144 h postrace. On their arrival to the finish line, participants were randomized into one of the three intervention groups: running (RUN), elliptical training (ELIP) and resting recovery (REST). RUN and ELIP groups exercised continuously for 40 min at a moderate intensity (95–105% of the HR corresponding to the first ventilatory threshold) at 48, 96 and 144 h after the marathon. Neither 'Intervention' factor nor 'Intervention x Time' interaction effects were revealed for muscle damage blood markers ( p  > 0.05). On the other hand, RUN group evidenced an enhancement in SJ performance 96 h post-marathon as compared with REST group (108.29 ± 10.64 vs 100.58 ± 9.16%, p  = 0.020, d  = 0.80). Consequently, return to running at 48 h post-marathon does not seem to have a negative impact on muscle damage recovery up to eight days post-race and it could be recommended in order to speed up neuromuscular recovery.